2015
DOI: 10.1111/rda.12504
|View full text |Cite
|
Sign up to set email alerts
|

Aquagrams of Raw Milk for Oestrus Detection in Dairy Cows

Abstract: The purpose of this research was to develop rapid and cost-effective method for oestrus detection in dairy cows by means of near infrared spectroscopy and aquaphotomics, using raw milk from individual cows. We found that aquaphotomics approach showed consistent specific water spectral pattern of milk at the oestrus periods of the investigated Holstein cows. Characteristic changes were detected especially in foremilk collected at morning milking. They were reflected in calculated aquagrams of milk spectra where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The water spectral patterns of blood, milk, and urine of mastitic cows, revealed that the same water absorbance bands are activated in different body fluids in response to the presence of disease [81]. Similarly, physiological changes such as ovulation can be detected in various body fluids using the same principles such as in the Giant panda [68,83], in the Bornean orangutan [84], in dairy cows [85] and in mares [86].…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…The water spectral patterns of blood, milk, and urine of mastitic cows, revealed that the same water absorbance bands are activated in different body fluids in response to the presence of disease [81]. Similarly, physiological changes such as ovulation can be detected in various body fluids using the same principles such as in the Giant panda [68,83], in the Bornean orangutan [84], in dairy cows [85] and in mares [86].…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…The classic aquagram shows the relative fingerprint, i.e., the WASPs, in the context of all spectra in the examined group [18,19,21,54].…”
Section: Calculation Protocol Of "Classic" Aquagrammentioning
confidence: 99%
“…One of the main visualization and analytical tools of aquaphotomics, is the so-called aquagram [ 8 , 18 ] which provides a comprehensible demonstration of the ratios of different water species present in a sample. Aquagrams have been found very useful in many applications, such as diagnosis of estrus in giant pandas [ 19 ], orangutans [ 20 ] and cows [ 21 ] and showing the different water spectral patterns of probiotic and non-probiotic bacteria strains [ 22 ], or for example, revealing different types of water in the soft contact lenses, in a completely nondestructive manner [ 23 , 24 , 25 ]. The cited references demonstrated the usefulness of the presentation of the water spectral patterns in aquagrams.…”
Section: Introductionmentioning
confidence: 99%
“…In the milk NIR spectra of Holstein cows, Takemura et al 8 reported similar aquagrams 9 to those of giant panda and orangutan although they used 11 slightly different wavelengths to the 12 wavelengths reported above as their WAMACS. Samples with low milk progesterone concentration, characteristic of the female in follicle phase, showed increased activity in the spectral region from 1494 nm to 1584 nm in which water has strong hydrogenbonded structures.…”
mentioning
confidence: 91%